ESTETIKA GASTRONOMI NUSANTARA DALAM MEDIA DIGITAL - Ilma Pratiwi (Universitas PGRI Adi Buana Surabaya, 2021)
The development of the digital technology affects how humans perceive aesthetics in digital media. Including how the Indonesia gastronomic presentation is perceived in digital media both visually and audio. Gastronomy is the study of food and food culture. The development of digital information technology creates a space that is full of information, how can information about the Indonesian gastronomy continue to exist in the midst of cross-cultural information on today's digital media. People's behavior is influenced by the perceptions of netizens formed from digital information media, be it social media, television media, film media, even entertainment media on demand. This study uses a phenological approach to describe how the Indonesian gastronomic aesthetics are presented in various digital media platforms, namely social media Instagram, social media Facebook, social media Youtube, digital television media, digital film media, and entertainment digital media on demand. The data was obtained through observation of these various digital media platforms. This study produces a comparison of the aesthetic elements used in each of these digital media and how the existence of Indonesian gastronomy is presented in it.